2020
DOI: 10.1177/2382120520931773
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Simulator-Based Crisis Resource Management Training on Collective Orientation in Anaesthesia: Pre-Post Survey Study With Interprofessional Anaesthesia Teams

Abstract: Theory: Individuals have different qualities, levels of willingness, and degrees of engagement for working in teams. This behaviour is termed ‘Collective Orientation’ (CO). Collective orientation can be trained and has a positive influence on team processes. Here, we investigated the effect of a simulator-based, Crisis Resource Management team training upon the participants’ CO. Hypotheses: We hypothesized (1) the scales of CO and Presence for lab-based microworld research (PLBMR) are applicable to the German … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
4
6
1
Order By: Relevance
“…There was no correlation between Presence and increase of CO. This result is similar to a study in which we observed experienced anaesthesia nurses and physicians and the change in CO as a function of Presence [ 21 ]. In both studies, the professional groups were represented by members of their professional field.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There was no correlation between Presence and increase of CO. This result is similar to a study in which we observed experienced anaesthesia nurses and physicians and the change in CO as a function of Presence [ 21 ]. In both studies, the professional groups were represented by members of their professional field.…”
Section: Discussionsupporting
confidence: 91%
“…Own experiences and the relevance of the topic are known determining factors for learning success [ 24 ]. The effect on the CO does not seem to depend on professional experience, as we have made the same observation with experienced anesthesiologists before [ 21 ]. As observed in a previous study, the effect of increased “Affiliation” does not occur, when the nurse is simulated by a physician [ 25 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…There was no correlation between presence and increase of CO. This result is similar to a study in which we observed experienced anesthesia nurses and physicians and the change in CO as a function of presence (21). In both studies, the professional groups were represented by members of their professional eld.…”
Section: Discussionsupporting
confidence: 89%
“…Own experience and the relevance of the topic are known determining factors for learning success (24). This effect of changed CO does not seem to depend on professional experience, as we have made the same observation with experienced anesthesiologists before (21). As observed in a previous study, this effect does not occur, when the nurse is simulated by a physician (25).…”
Section: Discussionsupporting
confidence: 85%